Attenuation of food allergy symptoms following treatment with human milk oligosaccharides in a mouse model. Issue 9 (26th May 2015) - Castillo‐Courtade, L.; Han, S.; Lee, S.; Mian, F. M.; Buck, R.; Forsythe, P.
Abstract Background The prebiotic nature of human milk oligosaccharides (HMOs) and increasing evidence of direct immunomodulatory effects of these sugars suggest that they may have some therapeutic potential in allergy. Here, we assess the effect of two HMOs, 2'‐fucosyllactose and 6'‐sialyllactose, on symptomatology and immune responses in an ovalbumin‐sensitized mouse model of food allergy. Methods The effects of oral treatment with 2′‐fucosyllactose and 6′‐sialyllactose on anaphylactic symptoms induced by oral ovalbumin (OVA) challenge in sensitized mice were investigated. Mast cell functions in response to oral HMO treatment were also measured in the passive cutaneous anaphylaxis model, and direct effects on IgE‐mediated degranulation of mast cells were assessed. Results Daily oral treatment with 2′‐fucosyllactose or 6′‐sialyllactose attenuated food allergy symptoms including diarrhea and hypothermia. Treatment with HMOs also suppressed antigen‐induced increases in mouse mast cell protease‐1 in serum and mast cell numbers in the intestine. These effects were associated with increases in the CD4+CD25+IL‐10+ cell populations in the Peyer's patches and mesenteric lymph nodes, while 6′‐sialyllactose also induced increased IL‐10 and decreased TNF production in antigen‐stimulated splenocytes. Both 2′‐fucosyllactose and 6′‐sialyllactose reduced the passive cutaneous anaphylaxis response, but only 6′‐sialyllactose directly inhibited mast cell degranulation in vitro, at high concentrations. Conclusions Our results suggest that 2′‐fucosyllactose and 6′‐sialyllactose reduce the symptoms of food allergy through induction of IL‐10+ T regulatory cells and indirect stabilization of mast cells. Thus, human milk oligosaccharides may have therapeutic potential in allergic disease.